Mutation c.1190-1delG/N in intron 8 and c.1708G>C/N in exon 12 not reported in the IDUA gene developed a clinical phenotype of Scheie syndrome. - Delgado, Wilmer; Miranda, Luis; Chávez, Carlos; Solis, Ernesto; Cammarata, Francisco (Investigación Clínica, 2014)
Mucopolysaccharidoses are a group of lysosomal storage disorders caused by deficiency of enzymes catalyzing the degradation of glycosaminoglycans. Mucopoly-saccharidosis I can present a wide range of phenotypic characteristics with three major recognized clinical entities: Hurler and Scheie syndromes represent phenotypes at the severe and mild ends of the clinical spectrum, respectively, and the Hurler-Scheie syndrome is intermediate in phenotypic expression. These are caused by the deficiency or absence of _-L-iduronidase, essential to the metabolism of both dermatan and heparan sulfate, and it is encoded by the IDUA gene. We report the case of a 34-year-old male patient with enzymatic deficiency of a-L-iduronidase, accumulation of its substrate and a previously unreported mutation in the IDUA gene that developed a phenotype of Scheie syndrome.